2002
DOI: 10.1111/j.1365-2621.2002.tb10310.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibitory Effect of Chicken Egg Yolk Antibody (IgY) onEscherichia coliO157:H7

Abstract: Escherichia coli O157:H7-specific antibodies (immunoglobulin Y [IgY]) were isolated by the waterdilution method from the egg yolk of chickens that were immunized with E. coli O157:H7 whole cells. The specificbinding activity of IgY against E. coli O157:H7 as determined by the enzyme immuno assay showed high levels of activity against bacterial whole cells. IgY binding activity was further demonstrated to have an inhibitory effect on E. coli O157:H7 growth in a liquid medium. The antibacterial function of IgY a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 47 publications
6
63
1
Order By: Relevance
“…Table 1 shows the serum IgG concentration in Leghorn chickens and Tsaiya ducks at the start of the trial and after the third immunization. After 3 immunizations (week 7 of the experiment), the serum IgG level in Leghorn layer hens and Tsaiya ducks were increased significantly, this outcome consistent experimental results obtained by Sunwoo et al (2002), who also indicated that the antibody titer peaks after 3 immunizations. …”
Section: Protein Quantification Purity Determination Of Igy and Titesupporting
confidence: 78%
“…Table 1 shows the serum IgG concentration in Leghorn chickens and Tsaiya ducks at the start of the trial and after the third immunization. After 3 immunizations (week 7 of the experiment), the serum IgG level in Leghorn layer hens and Tsaiya ducks were increased significantly, this outcome consistent experimental results obtained by Sunwoo et al (2002), who also indicated that the antibody titer peaks after 3 immunizations. …”
Section: Protein Quantification Purity Determination Of Igy and Titesupporting
confidence: 78%
“…The concentrations of total IgY and experimental conditions utilized in our growth inhibition assays were standardized in preliminary experiments, by modifications of previous reports (Sugita-Konishi et al, 1996;Lee et al, 2002;Sunwoo et al, 2002).…”
Section: Growth Inhibition Assaysmentioning
confidence: 99%
“…Recently, the utilization of IgY antibodies from the eggs of chickens which were immunized with pathogens has been the focus of attention in immunotherapy and diagnosis since the birds can actively transfer immunoglobulin to the egg yolk at the same concentration levels as in mammals (Buchwald and Profski 2003;Sunwoo et al 2002). The use of chicken antibody on a large scale offers several advantages, such as low costs, large yield and scaleable production and storability.…”
Section: Introductionmentioning
confidence: 99%